Bund Bildender Künstler Hagenring. (Hagen : Bund Bildender Künstler, 1990)
Bettermann, Hermann ; Birnschein, Alfred ; Birnschein, Marie-Luise ; Clemens, Heinz ; Deimel, Christoph ; Dröge, Johannes ; Drücke, Paul ; Eckstein, Ruth ; Elben, Helga ; Fritsch, Arwed ; Hagedorn, Ingeborg ; etc.
Bund Bildender Künstler Hagenring, Hagen, 1990
boek